The Sining Ritual Tradition in The Gayo Community of Central Aceh as A Form of Revitalization of Educational Values and Local Wisdom - Tengku Hartati; Ramdiana Ramdiana (MASI Mandiri Edukasi, 2026)
This research addresses the fading existence of the Sining ritual tradition among the Gayo community in Central Aceh, driven by modernization and globalization, which have diminished youth interest in this cultural heritage. The objective is to explore the educational values and local wisdom embedded in Sining and to examine its potential for revitalization as a source of character education. This study employs a literature review method with a qualitative approach. Data were gathered from books, scholarly journal articles, and research reports through documentary study. Analysis was conducted using qualitative content analysis, involving data reduction, presentation, and conclusion drawing. The results reveal that the Sining ritual holds deep symbolic and philosophical meanings, reflecting harmony with nature, gratitude, mutual cooperation, respect for ancestors, and a sense of divinity. It serves as a medium for transmitting values of character education, such as discipline, responsibility, teamwork, empathy, and social concern. Revitalizing Sining also plays a crucial role in preserving Gayo local wisdom, including botanical knowledge, traditional farming systems, and vernacular architecture. Furthermore, the tradition embodies social values that strengthen community solidarity and religious values that integrate Islamic teachings with local culture. The study concludes that Sining is a comprehensive cultural entity worthy of revitalization as a source of character education grounded in local wisdom.